Influence of high temperature stress on starch metabolism in two durum wheat varieties differing in heat tolerance - Bansal, Kavita; Munjal, Renu; Madan, Shashi; Arora, Vinita (Journal of Cereal Research, 2012)
The formation and characteristics of the grain is largely a function of starch biosynthesis. This study investigated the effect of high temperature during grain development on enzymes, metabolites and components of starch metabolism in two durum wheat (Triticum durum) varieties namely WH896 and WH912 differing in their response to high temperature. Activity of starch branching enzyme (SBE) was reduced by 38% in less sensitive variety (WH896) and by 43 per cent in more sensitive variety (WH912). The remarkable difference between the two cultivars was also observed in inorganic pyrophosphate and UDP – glucose level. Differential effects in amount of total soluble sugar and amylopectin were also observed. Magnitude of reduction in ADP-glucose and UDP-glucose metabolites was more in WH 896 (41.0%) and WH 912 (29.3%) under high temperature stress as compared to control. No correlation between the changes in sucrose and ADP – glucose concentration was observed at high temperature.